Before the silence (Piscataway, NJ)
345, [2] sayfa
Keywords: “This book is a collection of newspaper reports documenting the massacres and genocides of Greeks, Armenians, and Assyrian minorities who inhabited Asia Minor for many millennia, by the Ottoman Turks and later the Kemalists. These reports, emanating from English sources, show that there was a systematic and organized campaign by Turkish authorities to eliminate all traces of the memories of these minorities from the face of the earth“ -- Yayıncı.